(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
This article has no abstract. The first 100 words appear below: An outborn, 2 hours old male newborn was admitted at the neonatal intensive care unit due to delayed cry after birth and respiratory distress soon after birth. The baby was born at 39 weeks of gestation at another hospital to a 30 year old primi mother by lower uterine caesarian section due to the obstructed labor. Although the mother was not in regular antenatal checkup. Her pregnancy period was uncomplicated. The baby was limp and blue immediately after birth and was managed accordingly by the attending physician and was referred to the Neonatal Intensive Care Unit of Bangabandhu Sheikh Mujib Medical University for better management.